SELECTION OF SINGLE PLANTS OF SWEET POTATO (IPOMOEA BATATAS L.) RESULTS OF OPEN-CROSS IN FEMALE PARENT BETA-2 FOR ORANGE-FLESHED SWEET POTATO AND HIGH PRODUCTION - Ratna Dewi; Gut Tianigut; Febria Cahya Indriani (Proceedings of the 1st International Conference on Social Science (ICSS), 2023)
Sweet potato (Ipomoea batatas L.) is one of the alternative commodities in food diversification. Apart from being a source of carbohydrates, orange-fleshed sweet potatoes contain lots of beta-carotene (pro-vitamin A) and antioxidants that contribute greatly to health. Efforts to improve the quality of orange sweet potatoes in quantity and quality are still very much needed, one of which is by crossing. The study aimed to obtain high-yielding orange-fleshed sweet potato lines from free crosses between female parent Beta-2 and male parent local sweet potato Lampung (LPG-01, LPG-03, LPG-06, LPG-11), Cilembu, Ayamurasaki. The method used in this selection is a single planting selection method by looking at the morphological characters of each line. Single planting selection is the initial selection after successful crossing. The results showed that of the 79 lines that were crossed by a female parent of Beta-2, there were 19 lines with orange flesh and high yields, namely Beta2 OP1, Beta2 OP3, Beta2 OP4, Beta2 OP6, Beta2 OP8, Beta2 OP19, Beta2 OP25, Beta2 OP30, Beta2 OP33, Beta2 OP34, Beta2 OP36, Beta2 OP38, Beta2 OP42, Beta2 OP43, Beta2 OP54, Beta2 OP58, Beta2 OP63, Beta2 OP73, Beta2 OP77